Intercultural Communication and Applied linguistics - Extending Horizons: An Interview with Lixian Jin - Lun Peng (Gloria) (Cranmore Publishing, 2021)
At the start of this interview, Professor Jin recounts how she abandoned her ambition to become a physician and ended up teaching and researching clinical linguistics at a British university for 18 years. She emphasises the crucial role of intercultural communication (IC) in both foreign language education and the 'internationalisation' of universities; in connection with the former, she recommends some ways for EFL teachers to promote intercultural communication competence (ICC) in their TESOL practices; regarding the latter, she points out that for a university to be 'internationalised', true IC is indispensable as it can bring all partners (i.e. academic, administrative, technical staff and students) up to a level where they understand, empathize and appreciate each other. In her current role as Dean of Faculty of Humanities and Social Sciences in the City University of Macau, she has been leading a group of faculty members to work on proposals to establish Applied Linguistics programmes for BA, MA and PhD levels, in order to support the infrastructure of future workforces in Macau and the Greater Bay Area. Additionally, in the Chinese EFL context, she discusses several key issues concerning teaching English to young learners and to older learners (aged 50 and above). Finally, she offers some advice regarding how to balance the teaching, research, and administrative responsibilities expected of a faculty member in the field of applied linguistics.